Peran NGO Sebagai Advocacy Broker Dalam Konservasi Lingkungan: Studi Kasus Kerja Sama YKAN dan Forlika Dalam Konservasi Mangrove di Kabupaten Berau - Adi Nugraha; Khoirul Amin; Mohamad Dziqie Aulia Al Farauqi; Rizki Tegar Sembada (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the involvement of the Nusantara Nature Conservation Foundation (YKAN) in mangrove management in Berau Regency. This study explains how YKAN, as a broker organization in an advocacy network, encourages the local Forlika community to obtain resources from global partnerships. This study uses a qualitative descriptive method. The research data is sourced from primary data through interviews and uses primary data from relevant literature studies related to the research variables. The results of this study show that there is cooperation between each actor in international relations in managing mangrove areas in Berau Regency. YKAN's partnerships with global and local institutions give YKAN a strategic position in transnational advocacy networks. YKAN functions as a liaison that advocates for the needs of coastal communities at the international level, so that YKAN's role is to represent local communities in cross-actor cooperation in Berau Regency.